The response regulator CrsR positively regulates ansamitocin P-3 biosynthesis in Actinosynnema pretiosum - Zhang, Peipei; Zong, Gongli; Wang, Tengfei; Zhao, Shuangying; Sun, Ruoyi; Fu, Jiafang; Liu, Meng; Cao, Guangxiang (Frontiers in Microbiology, 2025)
Ansamitocin P-3 (AP-3), a maytansinoid antibiotic produced by Actinosynnema pretiosum, exhibits potent anticancer activity. However, its biosynthetic regulation in A. pretiosum remains largely unknown. Two-component systems (TCSs) are ubiquitous in actinomycetes and primarily regulate the biosynthesis of secondary metabolites. In this study, we identified a novel TCS, designated CrsRK, in A. pretiosum X47 through sequence analysis. Deletion of the response regulator gene crsR drastically decreased AP-3 production. RNA-seq revealed CrsR’s global regulatory role, significantly altering transcription of primary metabolic genes, especially those in purine metabolism. Crucially, the deletion of crsR also significantly downregulated transcription of the AP-3 biosynthetic genes, including asm7, asm10–15, asm21, asm23–24, asmAB, and asm43–47, which encode enzymes for multiple steps in AP-3 biosynthesis. Electrophoretic mobility shift assays confirmed direct binding of CrsR to promoters of asm21, asm43–44, and asm45–47 operons, indicating direct transcriptional control. Our results demonstrate that CrsR positively regulates AP-3 biosynthesis by directly and indirectly controlling transcription within the AP-3 biosynthetic gene cluster. In conclusion, this study elucidates the critical role of CrsR in AP-3 biosynthesis and expands our understanding of AP-3 regulatory mechanisms and TCS functions in A. pretiosum.